2013
DOI: 10.1016/j.vetpar.2012.12.060
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Babesia microti-like infection in red foxes (Vulpes vulpes) from Portugal

Abstract: The prevalence of piroplasm (order Piroplasmida) infection was assessed in blood and bone marrow samples from 91 red foxes (Vulpes vulpes) from northern, central and southern Portugal by means of molecular methods. PCR for the 18S rRNA gene of Babesia spp. followed by sequencing revealed 63 foxes positive for the Babesia microti-like piroplasm (syn. Theileria annae) (69.2%; 95% confidence interval [CI]: 58.7-78.5%) and one fox positive for Babesia canis (1.1%; 95% CI: 0.0-6.0%). Positivity to the B. microti-li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
56
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 41 publications
5
56
2
3
Order By: Relevance
“…Apart from domesticated dogs, B. canis has been molecularly confirmed in the neighbouring countries of Bosnia and Herzegovina from a single fox [17] and two captive grey wolves from Hungary [19] as well as in a single red fox (1/91) from Portugal [14]. Since data on Babesia infection in free-ranging carnivores are scarce, we performed a molecular and pathological investigation of Babesia and Theileria species infecting the free-ranging population of wolves from Croatia to understand the prevalence, distribution and potential health impacts of these parasites on a wild canid population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from domesticated dogs, B. canis has been molecularly confirmed in the neighbouring countries of Bosnia and Herzegovina from a single fox [17] and two captive grey wolves from Hungary [19] as well as in a single red fox (1/91) from Portugal [14]. Since data on Babesia infection in free-ranging carnivores are scarce, we performed a molecular and pathological investigation of Babesia and Theileria species infecting the free-ranging population of wolves from Croatia to understand the prevalence, distribution and potential health impacts of these parasites on a wild canid population.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike “B. vulpes”, B. canis has been reported only in a single animal during a study of the fox population in Portugal [14] and in a single fox in a similar survey in Bosnia and Herzegovina [17]. …”
Section: Introductionmentioning
confidence: 99%
“…[13] recently reviewed previous identifications of this parasite attributing many of them to B. capreoli . In contrast to ungulates, information on the occurrence and prevalence of piroplasmids in wild canids is limited [34]. In Europe, a continent where the Red fox is present at high densities [35], B. microti -like piroplasms were molecularly confirmed in foxes from Central and Northern Spain [9,36,37], Croatia [38] and Portugal [34].…”
Section: Introductionmentioning
confidence: 99%
“…In Europe, a continent where the Red fox is present at high densities [35], B. microti -like piroplasms were molecularly confirmed in foxes from Central and Northern Spain [9,36,37], Croatia [38] and Portugal [34]. In Portugal, a single fox was also found infected with B. canis [34]. Considering the relevant insights into piroplasm-wildlife epidemiology [39,40], the increasing importance of Babesia as an emerging zoonotic disease [2,10] and the lack of information on piroplasm epidemiology in Northwestern Italy [23], we widely investigated Babesia / Theileria infection prevalence in wild ungulates and carnivores from the Piedmont region (Italy) and their biomolecular characteristics, by amplifying and sequencing part of the V4 hyper-variable region of the 18S rRNA gene.…”
Section: Introductionmentioning
confidence: 99%
“…Babesia microti-like parasites -also known as Babesia sp., Babesia annae or Theileria annae -are frequently found in foxes in countries such as Croatia [7], Portugal [5] and Spain [8]. The common assumption is that Ixodes hexagonus is involved in the transmission cycle [9], and a recent study identified I. ricinus and I. canisuga as carriers and therefore as potential vectors [10].…”
Section: Introductionmentioning
confidence: 99%